The student movement at the Universidad Pedagógica y Tecnológica de Colombia 1971 - Bernal Villate, Sandra Liliana; Patiño, Diego Eduardo Naranjo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: This work focuses on the analysis of the student movement of the Universidad Pedagógica y Tecnológica de Colombia in 1971. Originality / contribution:The originality lies in the mobilization and proposals for student reform to achieve university co-government carried out by left-wing political groups in this institution. Method:The method is based on political history. Information gathering:The methodology and research strategies focused on the recovery of the memory of the protagonists, which was contrasted with the minutes of the academic and superior councils and the publications of the national press on the subject of student mobilizations. Conclusions:It is concluded that in this university, the internal divisions of the student collectives, together with the repressive policies of expulsion and the non-involvement of the social and union sector in the movement, diverted the path of a local negotiation that would have allowed the dream of university co-government to be fulfilled at that time. This was only achieved in Colombia until 1991 with the change of the country's political constitution.